2011
DOI: 10.1371/journal.pone.0024097
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptor and Caspase 1 Activation Are Central to Airway Inflammation Observed after Exposure to Tobacco Smoke

Abstract: Chronic Obstructive Pulmonary Disease (COPD) is a cigarette smoke (CS)-driven inflammatory airway disease with an increasing global prevalence. Currently there is no effective medication to stop the relentless progression of this disease. It has recently been shown that an activator of the P2X7/inflammasome pathway, ATP, and the resultant products (IL-1β/IL-18) are increased in COPD patients. The aim of this study was to determine whether activation of the P2X7/caspase 1 pathway has a functional role in CS-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 36 publications
(56 reference statements)
7
114
0
Order By: Relevance
“…These data are consistent with data suggesting that the cigarette smoke-induced inflammation is driven by the release of eATP resulting in P2X7 and subsequent inflammasome activation. Interestingly, the innate immune response was not altered in TRPV4 −/− mice challenged with an aerosol of LPS [138][139][140][141].…”
Section: Trpv4mentioning
confidence: 94%
“…These data are consistent with data suggesting that the cigarette smoke-induced inflammation is driven by the release of eATP resulting in P2X7 and subsequent inflammasome activation. Interestingly, the innate immune response was not altered in TRPV4 −/− mice challenged with an aerosol of LPS [138][139][140][141].…”
Section: Trpv4mentioning
confidence: 94%
“…Evidence for NLRP3 involvement in acute inflammation associated with CS exposure has been further studied in mouse models (39)(40). Nlrp3 2/2 mice displayed reduced caspase-1 activation, IL-18/IL-1b production, and neutrophil influx in the bronchoalveolar lavage (BAL) relative to wild-type mice after acute CS exposure (39).…”
Section: Inflammasomes In Airways Diseasesmentioning
confidence: 99%
“…Nlrp3 2/2 mice displayed reduced caspase-1 activation, IL-18/IL-1b production, and neutrophil influx in the bronchoalveolar lavage (BAL) relative to wild-type mice after acute CS exposure (39). Genetic deletion of the P2X7 receptor also reduced CS-induced caspase-1 activation, IL-1b release, and airway neutrophilia during acute CS exposure (40). Contrasting studies reported that pulmonary inflammation in response to acute CS exposure required IL-1b/a production and IL-1R, but was independent Recent studies indicate that both glucose metabolism and fatty acid (FA) synthesis may be linked to inflammasome activation (32,33).…”
Section: Inflammasomes In Airways Diseasesmentioning
confidence: 99%
“…However, there is evidence of inflammasome activation, since levels of caspase-1 are increased in lung tissue after CS challenge in mice. Caspase-1 levels are also higher in lung tissue from COPD patients and smokers than from nonsmoking donors (19). Selective inhibition of caspase-1 significantly decreased inflammation after CS challenge in animal models (11).…”
Section: Role Of the Inflammasome In Lung Diseasesmentioning
confidence: 99%